Molecular characterization and genetic diversity of parvoviruses prevalent in cats in Central and Eastern China from 2018 to 2022 - Pan, Shunshun; Jiao, Ruiqi; Xu, Xin; Ji, Jun; Guo, Ge; Yao, Lunguang; Kan, Yunchao; Xie, Qingmei; Bi, Yingzuo (Frontiers in Veterinary Science, 2023)
Cats are a potential source of genetic diversity for parvoviruses. Herein, 134 samples were collected from cats with clinical gastroenteritis and analyzed for the presence of viral DNA via polymerase chain reaction, which revealed 48 positive samples. Identity analysis of VP2 nucleotide sequences indicated that these 48 strains, belonging to feline panleukopenia virus (FPV) and canine parvovirus type-2 (CPV-2; including new CPV-2a and CPV-2c genotypes), shared 94.59%-99.94% nucleotide identity with the reference strains. The FPV strain F8 (isolated from Vietnam) appeared to be a recombinant of strains HB2003 and JS1901, whereas the Chinese CPV-2b strain BM-(11) isolated in 2011 was believed to be a recombinant of strains AH2008 and JS1901. In phylogenetic tree analysis based on VP2 nucleotide sequences, all obtained FPV strains and most reference FPV strains were clustered together, except strain BJ-22, which originated from monkeys. Further, two new CPV-2a strains (AH2005 and AH2008) were close to the newly reported Chinese CPV-2a strains but were distant from the other CPV-2a strains, namely CPV-339 (from the United States) and K022 (from South Korea). Additionally, the FPV and CPV-2 strains had high mutation rates in the antigenic regions of the VP2 protein. According to model prediction of the CPV-VP2 protein, these mutations may cause changes in the tertiary structure of VP2. The findings of this study can be used to improve the pre-evaluation of vaccination efficacy against diseases caused by FPV and CPV-2 in domestic cats and understand their genotypic transmission and mutation trends.